Me ajudem
![- 2^{2} +( \frac{2}{3}) ^{-2} - 2^{2} +( \frac{2}{3}) ^{-2}](https://tex.z-dn.net/?f=-+2%5E%7B2%7D+%2B%28+%5Cfrac%7B2%7D%7B3%7D%29+%5E%7B-2%7D++)
e
![- 2^{4} +(-3) ^{2} + 4^{0} - 2^{4} +(-3) ^{2} + 4^{0}](https://tex.z-dn.net/?f=-+2%5E%7B4%7D+%2B%28-3%29+%5E%7B2%7D+%2B+4%5E%7B0%7D+)
Soluções para a tarefa
Respondido por
0
Respondido por
0
-2² + (2/3)⁻² =
-2.2 + (3/2)² =
-4 + 9/4 =
m.m.c = 4
-16 /4+ 9/4 = -7/4
-2⁴ + (- 3)² + 4°
-2.2.2.2 + (+9) + 1 =
-16 + 9 + 1 = -6
-2.2 + (3/2)² =
-4 + 9/4 =
m.m.c = 4
-16 /4+ 9/4 = -7/4
-2⁴ + (- 3)² + 4°
-2.2.2.2 + (+9) + 1 =
-16 + 9 + 1 = -6
Perguntas interessantes
Filosofia,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás